2019
DOI: 10.1186/s12870-019-1795-x
|View full text |Cite
|
Sign up to set email alerts
|

Using RNA-seq to characterize responses to 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitor herbicide resistance in waterhemp (Amaranthus tuberculatus)

Abstract: Background Waterhemp ( Amaranthus tuberculatus (Moq.) J.D. Sauer) is a problem weed commonly found in the Midwestern United States that can cause crippling yield losses for both maize ( Zea mays L.) and soybean ( Glycine max L. Merr). In 2011, 4-hydroxyphenylpyruvate-dioxygenase (HPPD, EC 1.13.11.27) inhibitor herbicide resistance was first reported in two waterhemp populations. Since the discovery of HPPD-herbicide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 75 publications
1
28
0
Order By: Relevance
“…Previous work has found evidence of gene expression changes in response to herbicide, often in genes not previously known to be important for herbicide response (An et al 2014;Leslie and Baucom 2014;Duhoux et al 2015;Serra et al 2015;Zhao et al 2017;Wright et al 2018) , but not directly investigated whether plastic responses appeared to be adaptive. One hint at the importance of maladaptive plasticity comes from the observation that a susceptible population of Amaranthus tuberculatus had increased rapid (3 hour) expression response to herbicide compared to a naturally resistant population (Kohlhase et al 2019) , suggesting that plastic expression changes could be maladaptive.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has found evidence of gene expression changes in response to herbicide, often in genes not previously known to be important for herbicide response (An et al 2014;Leslie and Baucom 2014;Duhoux et al 2015;Serra et al 2015;Zhao et al 2017;Wright et al 2018) , but not directly investigated whether plastic responses appeared to be adaptive. One hint at the importance of maladaptive plasticity comes from the observation that a susceptible population of Amaranthus tuberculatus had increased rapid (3 hour) expression response to herbicide compared to a naturally resistant population (Kohlhase et al 2019) , suggesting that plastic expression changes could be maladaptive.…”
Section: Discussionmentioning
confidence: 99%
“…76 Transcriptomic studies have been conducted recently to identify candidate genes contributing to HPPD-inhibitor resistance in A. tuberculatus, with the underlying assumption that such genes will be more abundantly expressed in resistant plants. 77,78 As is often the case with such studies, a large number of candidate genesbut no 'smoking gun'were identified, and much more work is needed for functional validation.…”
Section: Hppd Inhibitorsmentioning
confidence: 99%
“…Furthermore, the emergence of -omics resources and capabilities provide promising opportunities not only to elucidate these mechanisms, but also to understand their regulation and evolution. For example, in the last 10 years, we have gone from generating a very rudimentary transcriptome 88 for A. tuberculatus to obtaining a very high quality transcriptome, 77 along with highquality reference genomes of both a female and male individual. 64,89 Recently, a herbicide-sensitive A. tuberculatus population has been isolated before becoming extinct and made publicly available (accession Ames 35 826 in the US National Plant Germplasm System).…”
Section: Future Outlookmentioning
confidence: 99%
“…2017 ; Shergill et al. 2018 ; Kohlhase et al. 2019 ) as well as for 2,4-D resistance ( Figueiredo et al.…”
Section: Introductionmentioning
confidence: 99%